The Appeal of Apoliticalism at the Intersection of Human Rights and Legal Violations - Fathurrahman, Deri; Riyanta, Stanislaus; Rustam, Muhammad Reza (Formosa Journal of Multidisciplinary Research, 2024)
This research explores the rise of apoliticalism at the intersection of human rights and legal violations in Indonesia. The objective is to examine how factors such as education, access to information, and trust in the political system influence apolitical attitudes and evaluate the legal frameworks governing political participation. The study uses a literature review method, analyzing academic journals, reports, and government data. Results indicate that while apoliticalism aligns with human rights principles, it threatens democratic legitimacy when widespread. The research concludes that balancing individual freedoms with collective responsibility is essential to mitigate the adverse effects of apoliticalism, ensuring both human rights protection and democratic participation.